2017
DOI: 10.1021/acs.langmuir.7b00254
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Selective Adsorption of Graphene on a Gel Surface: Toward Improving the Quality of Graphene Nanosheets

Abstract: Top-down graphene production via exfoliation from graphite produces a mass of graphene with structural variation in terms of the number of layers, sheet size, edge type, and defect density. All of these characteristics affect its electronic structure. To develop useful applications of graphene, structural separation of graphene is necessary. In this study, we investigate the adsorption behavior of different types of graphene fragments using a multicolumn gel chromatography system with a view to developing an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…On the other hand, graphene layers are not stable and prone to mold to a roll form. These sole layers may be stabilized by reacting them in organic and aqueous media [28,29]. Normally, the structure of graphene remains deformed due to the attachment of some atoms and chemicals.…”
Section: Materials Based On Graphenementioning
confidence: 99%
“…On the other hand, graphene layers are not stable and prone to mold to a roll form. These sole layers may be stabilized by reacting them in organic and aqueous media [28,29]. Normally, the structure of graphene remains deformed due to the attachment of some atoms and chemicals.…”
Section: Materials Based On Graphenementioning
confidence: 99%
“…Graphene, owing to its unique two-dimensional monolayer structure, has attracted the attention of researchers and exhibits many interesting potential applications. In particular, graphene oxide (GO) nanosheets bearing carboxyl, hydroxyl, and other oxygen-containing groups offer extraordinary potential for preparing functional nanocomposite materials with strong hydrophilicities and excellent retention performance of organic dyes. Due to these advantages, graphene has great possible applications in the field of water treatment. Some researchers found that the nanometer-scale pores in a single-layer freestanding graphene could effectively filter NaCl salt from water, and that ability was critically dependent on the pore diameter, with adequately sized pores allowing water molecules to pass while blocking ions. , It was found that by controlling the pore sizes and functional groups on the nanopores, a monolayer graphene membrane is extraordinarily useful for desalination .…”
Section: Introductionmentioning
confidence: 99%